Climate change impact on rainfall and temperature in Muda irrigation area using multicorrelation matrix and downscaling method - Nurul Nadrah Aqilah, Tukimat; Sobri, Harun (IWA Publishing, 2015)
Statistical downscaling model was used to generate 30-year climate trend of Kedah – the state which has the largest cultivation area in Malaysia, resulting from climate changes. To obtain a better predictors set, multicorrelation matrix analysis was added in the climate model as a screening tool to explain the multiple correlation relationship among 26 predictors and 20 predictands. The performance of the predictor set was evaluated statistically in terms of mean absolute error, mean square error, and standard deviation. The simulation results depict the climatic changing trend in this region in terms of temperature, rainfall, and wet and dry length compared to historical data captured from 1961 to 2008. Annual temperature and rainfall depth are expected to increase 0.2 °C per decade and 0.9% per year, respectively, from the historical record. The months of November and January are expected to receive the highest and lowest rainfall depth, respectively, because of the two monsoon seasons. The wet spell is estimated to be from May to November in the middle of Kedah. The annual dry spell shall be from January to March, and is expected to shorten yearly.